Dual‐band platform‐mounted HF/VHF antenna design using the characteristic mode theory. Issue 4 (14th February 2018) - Li, Mingjian; Behdad, Nader
Abstract : The design of a dual‐band antenna mounted on a military platform is presented. The antenna operates in both high‐frequency (HF) and very‐high‐frequency (VHF) bands and consists of two half‐loops mounted on the platform. When the two half‐loops are excited differentially, they act as coupling elements exciting the platform dominant characteristic mode. This generates a horizontally polarised radiation with maximum radiation towards to zenith. Due to the presence of the platform, the antenna bandwidth is increased compared with that of an isolated antenna. When the two half‐loops are excited in the common mode, they behave as an ultra‐wideband antenna with monopole‐like radiation in the VHF band. A diplexer is used to achieve dual‐band operation, which allows the antenna operating at both bands simultaneously. A 60:1 scaled antenna prototype and its feed network is fabricated and characterised. At the lower band, the antenna exhibits an impedance bandwidth of 2.8% for a voltage standing wave ratio (VSWR) better than 2.25:1 and a directional radiation pattern with horizontal polarisation. At the higher band, the antenna exhibits a VSWR better than 2.25:1 and monopole‐like radiation characteristics across 2:1 bandwidth. The impact of the presence of a realistic ground plane on the antenna performance is also studied and discussed.